RESPON MAHASISWA PGMI TERHADAP PLATFORM WAKELET UNTUK PEMBELAJARAN ONLINE DI MASA PANDEMI COVID-19 - Nashran Azizan; Maulana Arafat Lubis; Prana Ugiana Gio; Marhamah Marhamah (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2021)
The COVID-19 pandemic has caused many changes in various aspects of life, including in the education sector and the learning system. The application of learning and teaching from home policies for students and lecturers alike changes the face-to-face learning perspective online by utilizing various applications and platforms. This study aims to determine the effectiveness of Wakelet for higher education and the benefits of Wakelet in online learning. This research method is descriptive quantitative through a survey. The population of this study was students of the PGMI IAIN Padangsidimpuan study program semester 6. The sampling technique used in this study was probability sampling which included simple random sampling. The sample was determined based on the Slovin formula assisted by Microsoft Excel software, so the sample was 94 respondents. The data collection technique used a questionnaire by Google Form. Analysis of research data using descriptive statistics assisted by STATCAL and EAVIS software. The results showed that the Wakelet platform was categorized as effective and efficient for use in the university environment, especially in the PGMI IAIN Padangsidimpuan Study Program based on student responses at a percentage of 78.72%. The Wakelet platform is also easily accessible and innovative, varied, and creative based on student responses, which are 80.85%. Besides having an attractive appearance, the Wakelet platform also has benefits, including bringing together all types of student work collected, such as videos, article texts, images, PDF files of papers/e-books / e-journals / e-proceedings, sharing web links, media links,social media and others.